ANALISIS HUBUNGAN TINGKAT KAPABILITAS APARAT PENGAWASAN INSTANSI PEMERINTAH (APIP) DENGAN KUALITAS PENGELOLAAN KEUANGAN HALAMAN JUDUL - Nur Fajri (Master in Accounting Program, 2019)
Abstract The purpose of this study is to analyze the relationship between the level of government internal supervisory apparatus (APIP) capability and the quality of financial management. The researcher measured the quality of financial management of 42 local governments from various levels of APIP capability which are the research samples. The indicators used are the opinion of Supreme Audit Institution (BPK), the number of internal control weakness findings, the number of non-compliance findings, and the financial impact of non-compliance findings sourced from the financial audit report (LHP) of BPK on the local government financial statements (LKPD) for the fiscal year 2016. The result of the measurement was then compared and analyzed to determine the relationship between the level of APIP capability and the quality of financial management. Based on the analysis that had been done, it can be concluded that there is no significant relationship between the level of APIP capability and the quality of financial management. In addition, this study also identified factors that can explain why there is or there is no significant relationship between the level of APIP capability and the quality of financial management by conducting in-depth interviews with participants from the Sleman Regency Government, which is one of the research samples. Based on the analysis of interview transcripts and documents, it can be concluded that the absence of a significant relationship between the level of APIP capability and quality of financial management could be caused by the more dominant role of local government agencies (SKPD) in achieving the quality of financial management, the improvement of the level of APIP capability which is not followed by the significant improvement on the role and services of APIP, and the potential weakness during the process of assessment of the APIP capability.